Influence of psychological methods on personnel management ("Journal "U". Economy. Management. Finance.", 2023)
The article examines the influence of psychological methods on human resource management. The relationship between psychology and management is also reflected. Psychological methods of personnel management were evaluated.
Keywords: motivation; psychological methods; personnel management; management